PENGARUH DISIPLIN, KONFLIK KERJA, DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BALI ART SUPPLIES DENPASAR - Putu Erik Widiastuti; Ni Nyoman Ari Novarini; Ni Putu Ayu Sintya Saraswati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
Employees are human resources (HR) which is an important asset that controls the success or failure of acompany. Every organization wants and strives to get quality human resources to be able to achieve and realize the goals of the organization. This study aims to determine the effect of discipline, work conflict, and workload onemployee performance at PT. Bali Art Supplies Denpasar with a total sample of 45 employees. The sampling technique used is saturated sampling method. Data collection methods used are observation, interviews,documentation and questionnaires. The analysis technique used is multiple linear regression analysis through the SPSS version 25 program. Based on the results of the analysis, this study shows that work discipline has a positiveand significant effect on employee performance at PT. Bali Art Supplies Denpasar. The better the work discipline that exists at PT. Bali Art Supplies Denpasar, the better the employee performance. Work conflict has a positive and significant effect on employee performance at PT. Bali Art Supplies Denpasar. Increasing work conflict in companies will raise employee morale to be better than other employees and be able to improve employee performance. Workload has a positive and significant effect on employee performance at PT. Bali Art Supplies Denpasar. The existence of a balanced loading intensity between the existing work and the workforce will be able to improve employee performance.